Dualism of Sedulur Sikep Images in Documentary Film: Analysis of "Samin vs Semen" and "Sikep Samin Semen" Film - Namira Choirani Fajri (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2020)
"Samin vs Semen" and "Sikep Samin Semen" are documentary films that raised Orang Samin as the main character in the story. This article aims at looking at the depiction of sedulur sikep (Orang Samin) in two documentaries, so that the needs can be identified. The method used is the genre analysis method. Through genre analysis, construction or building art production can be concluded by the audience. The image of Sedulur Sikep in the film Samin vs Semen" and "Sikep Samin Semen" different. The existence of the dualism of the image of Sedulur Sikep shows that the documentary film which is considered to represent reality cannot show a single sound. As a communication medium, film still represents the voice of its maker so that it cannot be seen as absolute truth.